Prolonged exposure of colon cancer cells to 5-fluorouracil nanoparticles improves its anticancer activity - Essam Tawfik; Maqusood Ahamed; Abdulaziz Almalik; Mohammad Alfaqeeh; Aws Alshamsan (Elsevier, 2017)
In this study, we aimed to improve the anticancer effect of 5-FU on human colon cancer cell lines by incorporating in poly(d,l lactic-co-glycolic acid) (PLGA) nanoparticles (NPs). The 5-FU-PLGA NPs were prepared by nanoprecipitation technique. Prepared NPs were moderately dispersed with an average diameter of 133 ± 25.19 nm. Scanning Electron Microscope (SEM) images revealed spherical structures with subtle surface irregularity. Free 5-FU dose-response curves were constructed (12.5-2000 μM) using MTT assay on HCT 116 and HT-29 cell lines for 1, 3, and 5 days. The calculated IC50 on HCT 116 were 185 μM after 1 day, 11.3 μM after 3 days, and 1.48 μM after 5 days. On HT-29, IC50 was only reached after 5 days of 5-FU treatment (11.25 μM). The HCT 116 viability following treatment with 100 μM 5-FU in free or NPs forms for 3 days was 38.8% and 18.6%, respectively. Similarly, when 250 μM was applied, HCT 116 viability was 17.03% and 14.6% after treatment with free and NPs forms of 5-FU, respectively. Moreover, HT-29 cell viability after 250 μM 5-FU treatment in free or NPs forms was 55.45% and 34.01%, respectively. We also noticed that HCT 116 cells were more sensitive to 5-FU-PLGA NPs as compared to HT-29 cells. Overall, our data indicate that 5-FU activity is time dependent and the prolonged effects created by PLGA NPs may contribute, at least in part, to the noticed enhancement of the anticancer activity of 5-FU drug.